Community health care workers' risk perception of occupational exposure to HIV in Ibadan, south-west Nigeria - Adamo A. Akinboro; Olabisi P. Adejumo; Comfort A. Onibokun; Eunice A. Olowokere (AOSIS, 2012)
Background: The ultimate goal of all healthcare workers (HCWs) is to maintain a healthy population and environment, and to adequately manage any condition that might constitute a menace to the health of the population at large. However, the central problem arising from the perception of risk of occupationally transmitted Human Immunodeficiency Virus (HIV) infection amongst HCWs is that it may distract them from giving quality healthcare. Objectives: The study aimed at addressing the following objectives: to explore the effects of level or years of experience on risk perception regarding occupational exposure to HIV, to assess HCWs' daily work routines' consistency in accordance with universal precaution guidelines, to determine HCWs' perception of workplace safety climate and identify factors that may constitute constraints to HCWs in adhering to universal precaution measures. Method: A descriptive cross-sectional survey design was utilised, using a triangulation method of data collection which involved the use of a questionnaire and direct observational methods using checklists. A total of 143 HCWs were purposively selected to form the study population. Results: The study showed a very high risk-perception amongst HCWs regarding occupational exposure to HIV and AIDS but a poor compliance with universal precautions in their professional duties. HCWs perception of risk and workplace safety climate did not influence their compliance with universal precautions (Pr > F = 0.2566; Pr > F = 0.2776). Conclusion: The need for policy guidelines to manage all aspects of risk-perception and practices of HCWs regarding HIV and AIDS in the healthcare settings most especially at the primary health care level need to be considered.